Assessment of the severity of atopic dermatitis - Agnieszka Bożek; Adam Reich (Termedia Publishing House, 2016)
Atopic dermatitis is a frequent, chronic and recurrent inflammatory skin disease with complex etiology. Typical symptoms of this disease are persistent itching and dry skin. To assess the severity of the disease we use various measuring methods. Currently, over 20 different measurement scales have been developed, of which the Scoring Atopic Dermatitis Index (SCORAD) and Eczema Area and Severity Index (EASI) are best known. Other methods for measuring the severity of atopic dermatitis include: Investigators' Global Assessment (IGA), Patient-oriented Eczema Measure (POEM), Six Area, Six Sign Atopic Dermatitis (SASSAD), Three Item Severity (TIS), Simple Scoring System (SSS), Basic Clinical Scoring System (BCSS), Patient-Oriented Scoring of Atopic Dermatitis (PO-SCORAD), Self-Administered Eczema Area and Severity Index (SA-EASI), Index for Atopic Dermatitis (W-AZS), Atopic Dermatitis Antecubital Severity (ADAS), Objective Severity Assessment of Atopic Dermatitis (OSAAD), and Visual Analogue Scale (VAS). There is no recommendation as to which scale is the most reliable in daily clinical practice. The international working group HOME (Harmonising Outcome Measures for Eczema) recommends EASI and POEM in atopic eczema trials.